Mechanical engineers' handbook. Volume 3 : Manufacturing and management - Kutz, Myer (John Wiley & Sons, Inc., 2015)
"This third volume of Mechanical Engineers' Handbook covers Manufacturing & Management, and provides accessible and in-depth access to the topics encountered regularly in the discipline: environmentally benign manufacturing, production planning, production processes and equipment, manufacturing systems evaluation, coatings and surface engineering, physical vapor deposition, mechanical fasteners, seal technology, statistical quality control, nondestructive inspection, intelligent control of material handling systems, and much more"--Provided by publisher